Probing Small-Angle Molecular Motions with EPR Spectroscopy: Dynamical Transition and Molecular Packing in Disordered Solids - Sergei A. Dzuba (Magnetochemistry, 2022)
Disordered molecular solids present a rather broad class of substances of different origin—amorphous polymers, materials for photonics and optoelectronics, amorphous pharmaceutics, simple molecular glass formers, and others. Frozen biological media in many respects also may be referred to this class. Theoretical description of dynamics and structure of disordered solids still does not exist, and only some phenomenological models can be developed to explain results of particular experiments. Among different experimental approaches, electron paramagnetic resonance (EPR) applied to spin probes and labels also can deliver useful information. EPR allows probing small-angle orientational molecular motions (molecular librations), which intrinsically are inherent to all molecular solids. EPR is employed in its conventional continuous wave (CW) and pulsed—electron spin echo (ESE)—versions. CW EPR spectra are sensitive to dynamical librations of molecules while ESE probes stochastic molecular librations. In this review, different manifestations of small-angle motions in EPR of spin probes and labels are discussed. It is shown that CW-EPR-detected dynamical librations provide information on dynamical transition in these media, similar to that explored with neutron scattering, and ESE-detected stochastic librations allow elucidating some features of nanoscale molecular packing. The possible EPR applications are analyzed for gel-phase lipid bilayers, for biological membranes interacting with proteins, peptides and cryoprotectants, for supercooled ionic liquids (ILs) and supercooled deep eutectic solvents (DESs), for globular proteins and intrinsically disordered proteins (IDPs), and for some other molecular solids.